Indicators of environmental performance evaluation – theory and corporate case study - Péterné Baranyi, Rita; Harazin, Piroska (International Journal of Engineering and Management Sciences, 2019)
In the last decades there was a change in the field of corporate performance evaluation. Performance management systems, indicator-based systems and new, intellectual capital-based evaluation systems have appeared. Finally new, wide range of corporate evaluating methods was born in theory and in practice too. It is also important to mention, that in a life of organizations there is an improvement in the activity in connection with sustainable development, and also in the usage of methods connecting to sustainable development. Therefore the evaluation in the dimensions of sustainability – in a case of environmental performance evaluation, or evaluation of corporate social responsibility – became more and more emphasised. We concentrate on the theory and practice of environmental performance evaluation. Summarize – based on definitions – the concept of environmental performance evaluation. We concentrate on peculiarities of environmental performance indicators – based on international standards and literature review; and also mention the characteristics of indicator systems. Based on theory, the practice is also important. Therefore we present a case study of a multinational company.